The pedagogical value of conceptual metaphor for secondary science teachers. Issue 5 (30th May 2018) - Daane, Abigail R.; Haglund, Jesper; Robertson, Amy D.; Close, Hunter G.; Scherr, Rachel E.
Abstract: The abstract nature of energy encourages metaphorical language. In educational settings, teachers and students use conceptual metaphors subconsciously to express their ideas about what energy is or how it functions in particular scenarios. However, research on scientific analogies and metaphors has predominantly focused on explicit instructional analogies, rather than implicit, everyday metaphor. In professional development for secondary science teachers, we sought to make explicit the embeddedness and ubiquity of conceptual metaphor in everyday language and in science—particularly, in energy—to expand teachers' understanding of their students' ideas. In our microcase study, we observed and video recorded four secondary teachers discussing metaphor. We used interaction analysis methods, focusing on how both discursive and nonverbal interactions between people, objects, and environment change over time, to analyze the collected data. We found evidence of teachers' (1) learning about conceptual metaphor theory and (2) finding value in understanding conceptual metaphor in educational settings. In particular, teachers acknowledged that if they identify implicit metaphors in students' science language, they will better understand students' ideas about energy. We present possible mechanisms for teacher learning about and valuing of energy metaphor; we also suggest how to support teachers in noticing and valuing metaphors for energy instruction.